Egg parasitism of Tuta absoluta by Trichogramma pretiosum in different genotypes of tomato - Gervásio, Rita de Cássia Rodrigues Gonçalves; Ciociola, Américo Iorio; Cecília, Lenira Viana Costa Santa; Maluf, Wilson Roberto (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this research was to evaluate the influence of 2-tridecanone (2-TD) content on three tomato genotypes (TOM-556, HI-1 and PI 134417) in the parasitism of eggs of Tuta absoluta Meyrick, 1917 by Trichogramma pretiosum Riley, 1879. Two experiments were carried out to verify the parasitism in isolated and combined plants. The results in both experiments showed that the percent of parasitism of TOM-556 was significantly higher than the HI-1 and PI 134417. A higher percent of parasitism was observed in all strains when the eggs were placed in isolated plants. It is supposed that the presence of genotypes with different concentration of 2-TD in the same environment may have influenced the parasitic behavior of T. pretiosum.